EKSPLORASI ARSITEKTUR KAWASAN PECINAN DI KAMPUNG KETANDAN LOR, YOGYAKARTA - Panggabean, Siti Munawarah; Wijono, Djoko (SENADA (Seminar Nasional Manajemen, Desain dan Aplikasi Bisnis Teknologi), 2021)
Chinatown has existed in Indonesia since the 5th century AD. The culture they bring is not only unique but also affects the space in which they live. This research is an exploration of chinatown architecture concept in Ketandan lor area, Yogyakarta. The target of this study is to find out the configuration of the space created is associated with the concept of cosmology and the characteristics of chinatown architecture in general. This qualitative method of research will use an approach based on direct observation, then analyzed with the researcher's interpretation. The results of this study mentioned that the Concept of Cosmology is not applied thoroughly and there are some differences in the characteristics of Chinatown that are influenced by adaptation to the local environment. This result is expected to increase knowledge about chinatown architecture and can be a consideration for regional management..